From metal–organic frameworks to magnetic nanostructured porous carbon composites: towards highly efficient dye removal and degradation1. Issue 11 (7th February 2015) - Zhang, Cong; Ye, Fanggui; Shen, Shufen; Xiong, Yuhao; Su, Linjing; Zhao, Shulin
<x xml:space="preserve">Abstract</x> A magnetic nanostructured porous carbon material (γ-Fe2O3/C) was easily synthesized using a microwave-enhanced high-temperature ionothermal method with an iron terephthalate metal–organic framework-MIL-53(Fe), as a template.